THE CONSEPT OF ECONOMIC DIVERSIFICATION AND ITS MACROECONOMIC SIGNIFICANCE - Ergasheva Dilnavoz Khazmaevna (Ecominds Press, 2025)
This article examines the term diversification, its role and significance in the process of globalization, as well as its place in the service sector, providing definitions and analysis of various types of diversification. It highlights how diversification can help in a competitive market environment by ensuring financial stability, allowing a company to secure its market niche, assessing risks, properly allocating resources, ensuring resilience to economic downturns, and addressing industry-specific challenges. The article also provides information on how service diversification can increase the number of clients and achieve their loyalty.
Keywords: Horizontal diversification, vertical diversification, lateral diversification, concentric diversification, centralized diversification, service diversification, company brand image, market diversification, competitiveness.